DESKRIPSI KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL EKSPONEN KELAS X SMA - Imelda Agustin Rostiana; Indrie Noor Aini (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
This research is to describe the mathematical understanding ability of high school students on exponential material based on the achievement of each indicator of mathematical understanding. This type of research is a qualitative descriptive research. The subjects in this study were high school students Class X for the academic year 2021/2022 in the Karawang area which consisted of 3 students. The research sample was obtained through a purposive sampling technique, namely taking samples with certain considerations. The data collection technique used a test instrument which consisted of 3 description questions. Data were analyzed descriptively. The data analysis technique used is qualitative data analysis with data reduction steps, data presentation and conclusion drawing. The results of the analysis of this study indicate that the ability of students to solve exponential problems based on indicators of understanding is quite good. The results showed that on average students were able to understand the problem, students were able to understand the concept of the exponential equation, and students were able to adjust the exponential equation formula to the problem solving. However, there are errors where students have not been able to determine the set of solutions correctly.